Induced global risk preference - Fabella, Raul V. (Economics Letters)
Risk preference may be induced by scale economies unrelated to taste structure. For an important set of functions exhibiting scale economies, we give (a) the necessary condition for global risk preference induction, and (b) sufficient conditions that preserve risk aversion.